Adoption of internet banking services in Gujarat: An extension of TAM with perceived security and social influence. Issue 1 (5th February 2018) - Patel, Kiran J.; Patel, Hiren J.
Abstract : Purpose: The purpose of this paper is to validate the technology acceptance model (TAM) and its extended form to understand the factors influencing internet banking adoption in Gujarat. Design/methodology/approach: Extended TAM incorporates perceived security and social influence, important variables in internet banking literature. Using a questionnaire survey, data relating to the variables are collected from 284 individuals who are/were using internet banking services and subjected to confirmatory factor analysis (CFA) to establish validity and structural equation modeling (SEM) to identify important factors influencing internet banking adoption. Findings: The empirical results of SEM showed that the extended TAM has higher predictability than the TAM in internet banking settings. The results highlighted that the intention to use internet banking is positively influenced mainly by perceived security, followed by other significant factors, namely, perceived usefulness, perceived ease of use and social influence. Practical implications: The findings of this paper enable internet banking service providers to develop/modify new/existing internet banking services in order to achieve higher adoption rates of internet banking. Originality/value: Additional incorporated variables in a new model considerably contribute to improving the understanding of internet banking adoption in Gujarat.